Family environment and school learning as predictors of financial literacy in elementary school students - Putri, Sarah Anida; Heryani, Rina (Institut Agama Islam Negeri Kendari, 2026)
Financial habits and attitudes formed during elementary school have a long-term impact on an individual’s financial well-being. This study aims to determine how the family environment and school learning influence financial literacy among elementary school students, focusing on three dimensions: knowledge, attitudes, and behavior. A quantitative, survey-based approach was used, involving 410 elementary school students from various schools in Lembang District, West Bandung Regency. Data analysis was conducted using linear regression. The results indicate that the family environment and school learning are significant predictors of students’ financial literacy, with a combined contribution of 12.1% to the variance. Notably, school learning demonstrated a stronger influence, suggesting that structured financial education in the classroom plays a significant role alongside family socialization. These findings highlight the need for integrated financial literacy programs involving teachers and parents, offering practical effectiveness for early financial education curriculum and policy development in Indonesia.